Exact asymptotic expansion for the resistance between the center node and a node on the cobweb network boundary - Izmailian, N.; Kenna, R. (Condensed Matter Physics, 2014)
We analyze the resistance between two nodes in a cobweb network of resistors. Based on an exact expression, we derive the asymptotic expansions for the resistance between the center node and a node on the boundary of the M x N cobweb network with resistors r and s in the two spatial directions. All coefficients in this expansion are expressed through analytical functions. Ми аналiзуємо опiр мiж двома вузлами в павутиннiй мережi резисторiв. На основi точного виразу ми
виводимо асимптотичнi розклади для опору мiж центральним вузлом i вузлом на границi павутинної
мережi M ×N з резисторами r i s у двох просторових напрямках. Всi коефiцiєнти в цьому розкладi виражаються через аналiтичнi функцiї.